2004
DOI: 10.1016/j.febslet.2004.05.067
|View full text |Cite
|
Sign up to set email alerts
|

The α4 and α7 subunits and assembly of the 20S proteasome

Abstract: The detailed mechanism of eukaryotic 20S proteasome assembly is currently unknown. In the present study, we demonstrate that the 20S proteasome subunits a4 and a7 interact with each other as well as all the a-subunits in vivo and in vitro. The N-terminal parts of a4 and a7 are essential for these newly discovered interactions in vitro. Glycerol gradient centrifugation of soluble extracts of HEK293 cells and Western blot analyses show that several a-subunits are found in non-proteasomal lowdensity fractions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 31 publications
3
17
0
Order By: Relevance
“…GRA6 binds to the proteasome subunit, α type, 4 (PSMA4). Proteasomes, multicatalytic proteinase complexes, are distributed throughout eukaryotic cells at a high concentration and cleave peptides in an ATP/ubiquitin-dependent manner in a non-lysosomal pathway (Coux et al, 1996;Apcher et al, 2004). An essential function of a modified proteasome, the immunoproteasome, is involved in the processing of class I MHC peptides.…”
Section: Discussionmentioning
confidence: 99%
“…GRA6 binds to the proteasome subunit, α type, 4 (PSMA4). Proteasomes, multicatalytic proteinase complexes, are distributed throughout eukaryotic cells at a high concentration and cleave peptides in an ATP/ubiquitin-dependent manner in a non-lysosomal pathway (Coux et al, 1996;Apcher et al, 2004). An essential function of a modified proteasome, the immunoproteasome, is involved in the processing of class I MHC peptides.…”
Section: Discussionmentioning
confidence: 99%
“…GRA6 binds to proteasome subunit, αtype, 4 (PSMA4). Proteasomes, multicatalytic proteinase complexes, are distributed throughout eukaryotic cells at a high concentration and cleave peptides in an ATP/ubiquitin-dependent process in a non-lysosomal pathway [61,62]. An essential function of a modified proteasome, the immunoproteasome, is the processing of class I MHC peptides.…”
Section: Gra6mentioning
confidence: 99%
“…Indeed, MG132 in combination with 17-AAG induced the complete disappearance of the NS3 (Figure 1D), suggesting that the reduction of HCV NS3 induced by treatment with the proteasome inhibitor MG132 was dependent on the HCV IRES. NNC#2 and #50-1 cells have different virus IRESs, known as the HCV IRES [25][26][27] and the encephalomyocarditis virus (EMCV) IRES [28], and HCV IRES-mediated translation is induced by PSMA7 [29]. The PSMA7 activity is blocked by MG132 [30].…”
Section: Resultsmentioning
confidence: 99%
“…In our assays, when Huh-7 cells exposed to MG132 were transfected with pHCV IRES luc or pEMCV IRES luc, HCV IRES activity was inhibited, but EMCV IRES was not ( Figure 2B). Apcher et al [29] reported that HCV IRES-mediated translation can be induced by PSMA7. The proteasome inhibitor MG132 inhibits PSMA7 activity.…”
Section: Discussionmentioning
confidence: 99%